If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49 + -3x = 8x Solving 49 + -3x = 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 49 + -3x + -8x = 8x + -8x Combine like terms: -3x + -8x = -11x 49 + -11x = 8x + -8x Combine like terms: 8x + -8x = 0 49 + -11x = 0 Add '-49' to each side of the equation. 49 + -49 + -11x = 0 + -49 Combine like terms: 49 + -49 = 0 0 + -11x = 0 + -49 -11x = 0 + -49 Combine like terms: 0 + -49 = -49 -11x = -49 Divide each side by '-11'. x = 4.454545455 Simplifying x = 4.454545455
| 3x+(-3)+-6= | | 1x+2x=2 | | 5/7-2x=4 | | 2-3x+4-5x+6+9x=14 | | -5(x+2)-43=8-21 | | 4(4x+3)-6(x+3)=18-2 | | 4/30 | | (-18)-(-22)= | | Y-4+2y=11 | | 7=6+q | | 20=3.14(HR^2) | | 7=6x-4 | | x/-8=-2-(-8) | | 2/3*72 | | 8x+16-7x=-6-10 | | 5y-30= | | -(8x^2-64)= | | 57y=14(4y+16) | | 7v=-28 | | 6m^2-18m-168= | | 8-8=7x+2x | | 1/2(6x-4)-2/3(12x+12)x=5 | | 56=9t-17t | | 68=4x-8 | | 9f-21=3(t-7)+6f | | 0.92x+0.96(12-x)=11.28 | | 17-15=x/-16 | | 2x=10-(-10) | | x(5x-2)(x+8)= | | 6w-9w=-18 | | m+4m-6m+3= | | 133.58=2.45h+72.33 |